ANALISIS SATUAN RODA DUA (SRD) DI SIMPANG BERSINYAL JAMBO TAPE - Rosa Sajida; Sugiarto Sugiarto; Yusria Darma (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
Many cities in Indonesia both small towns and big cities, the transportation system is dominated by motorcycle. The ownership of motorbikes has increased significantly in many cities due to their high mobility and affordable prices. The Increasing motorcycle users will make a major contribution to the traffic congestion on the highway; this makes motorbikes dominate traffic in the city. From previous studies the composition of vehicles in the Jambo Tape intersection was seen from traffic conditions consisting mostly of 70% motorcycle (MC), the larger the size of the vehicle, the more larger the proportion of a vehicle in a traffic flow The dominance of motorbikes in saturation flow at intersections it make motorbikes are considered as the basic vehicle for traffic flow. In Banda Aceh, especially in the Jambo Tape signal intersection, there is a mixed traffic flow which is dominated by two-wheeled vehicles. Then the movement of the traffic flow is not moving in one line (indiscipline lane), even the driver often makes lane changing or overtaking. The purpose of this study is to determine the equivalent value of two-wheeled vehicle at Jambo Tape signal intersection, also comparing the result of field observation analysis with EMP values, the saturate flow in previous research, and MKJI 1997. The research method used in this study is multiple linear regressions. The result obtained from this study is the new EMP value, for motorcycle (MC) 0,17; heavy vehicle (HV) 2,08 and rickshaw (RS) 1,3 and for the ERD value is light vehicle (LV) 5,97, heavy vehicle (HV) 12,41 and for the rickshaw (RS) 7,77. Furthermore, for the analysis the currents of saturated flow, two models were obtained, for the first model by not using constants is S0 = 488 We and for the second model that using constants is S0 = 1029 + 347 We